2000
DOI: 10.1006/brcg.1999.1203
|View full text |Cite
|
Sign up to set email alerts
|

Covert Processing of Faces in Prosopagnosia Is Restricted to Facial Expressions: Evidence from Cross-Modal Bias

Abstract: We present a single case study of a brain-damaged patient, AD, suffering from visual face and object agnosia, with impaired visual perception and preserved mental imagery. She is severely impaired in all aspects of overt recognition of faces as well as in covert recognition of familiar faces. She shows a complete loss of processing facial expressions in recognition as well as in matching tasks. Nevertheless, when presented with a task where face and voice expressions were presented concurrently, there was a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…A striate cortex lesion is associated with loss of conscious vision, which might be assumed to be necessary for intersensory binding. Such a view is inconsistent with the finding that crossmodal effects can be covert (15). Beyond that, it fails to explain why there is a difference in binding between voices with scenes, on the one hand, and faces, on the other hand.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A striate cortex lesion is associated with loss of conscious vision, which might be assumed to be necessary for intersensory binding. Such a view is inconsistent with the finding that crossmodal effects can be covert (15). Beyond that, it fails to explain why there is a difference in binding between voices with scenes, on the one hand, and faces, on the other hand.…”
Section: Discussionmentioning
confidence: 76%
“…Electrophysiological recordings of the time course of the crossmodal bias from the face to the voice indicated that such intersensory integration takes place on-line during auditory perception of emotion (12,13) and mainly translates as amplitude change of exogenous auditory components [i.e., early auditory potential (N1) and mismatch negativity (MMN)]. Importantly, facial expressions can bias perception of an affective tone of voice even when the face is not attended to (14) or cannot be perceived consciously, as is the case with brain damage to occipitotemporal areas (15). These latter findings indicate that the crossmodal effect does not depend on conscious recognition of the visual stimuli.…”
mentioning
confidence: 99%
“…(Bowers et al, 1985, de Gelder et al, 2000 and, more recently, neuroimaging (e.g., (Kanwisher et al, 1997, Ishai et al, 1999 findings suggest that selective brain regions within the occipito-temporal cortex make distinct contributions to the complex process of face perception. The superior temporal sulcus (STS), a region located in the lateral occipitotemporal cortex, is suggested to process dynamic facial properties (Puce et al, 1998, Hoffman and: that is, structural elements that can change from moment to moment, such as the direction of gaze and emotional expressions, both of which play important roles in social interactions (Allison et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We also presented neutral faces with minimally congruent neutral nonverbal vocal signals (i.e., polite coughs) to determine the extent to which integration mechanisms are engaged for facial-vocal pairings irrespective of congruence, because it has been suggested that facial and vocal integration is a mandatory process (10,17). To test whether a supra-additive response would be observed in the STS during AV presentation of emotion, we presented participants with unimodal faces (V condition) and nonverbal vocal expressions (A condition).…”
mentioning
confidence: 99%